A Generalized Learning Curve Adapted for Purchasing and Cost Reduction Negotiations. (13th February 2013) - Wong, Lam F.
Abstract : This paper presents the use and validation of a generalized learning curve in the economies of scale purchasing experience. The model, based on Wright's curve, incorporates two extra degrees of freedom to accommodate initial purchases of multiple (instead of single) units and a finite asymptotic price at high volumes. The study shows that each time the part purchase quantity is doubled, the price is reduced either by a constant percentage (a learning rate) or by an approach to an asymptotic plateau rate indicating a point of diminishing returns. Supplier price quotations at multiple purchase quantities were obtained for a pool of 17 critical parts. The data were fitted with the generalized learning curve by the method of least squares regression. The regressed learning rate, first unit price, and the asymptotic price can be used to infer supplier pricing strategies. Coupled with a "should-cost" analysis based on estimates of standard time and material, a system cost reduction task was carried out by the supply chain organization.